Empyema Thoracis: A Comprehensive Literature Review - Rani, Alfi Salma Q; Alifa, Baiq Salwa Nadira; Rahmansyah, M. Badzlul; Lazuara, Atiella Denisa Puriarta; Lestari, Rina (Jurnal Biologi Tropis, 2026)
Empyema thoracis is a severe pleural infection characterized by the accumulation of purulent fluid within the pleural cavity, most commonly as a complication of pneumonia. Delayed diagnosis and inadequate treatment contribute to increased morbidity and mortality. This review aimed to synthesize recent evidence on the epidemiology, pathophysiology, diagnosis, and management of empyema thoracis, highlighting current advances in clinical practice. A literature review was conducted using articles retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar published between 2015 and 2025. A total of 48 eligible articles, including original studies, systematic reviews, and international clinical guidelines, were analyzed. The findings indicate that disease stage at presentation and timely pleural drainage are the most consistent prognostic factors. Early-stage empyema is generally managed successfully with antibiotics and image-guided pleural drainage, whereas delayed treatment often requires surgical intervention, including video-assisted thoracoscopic surgery or decortication. The novelty of this review lies in integrating recent evidence and clinical guidelines to compare stage-based diagnostic and therapeutic approaches. Early multidisciplinary management with treatment tailored to the stage of empyema is essential to improve clinical outcomes, reduce complications, and support evidence-based decision-making in clinical practice.